STYLISTIC EQUIVALENCE AND CHALLENGES IN ENGLISH–UZBEK TRANSLATION - Bozorova Vasila Ilkhomovna (International Journal of Literature and Language Studies, 2026)
This article explores the linguistic, pragmatic, and structural challenges of achieving stylistic equivalence in English–Uzbek audiovisual translation (AVT), focusing on subtitling and dubbing. Translating from a low-context, analytic, Germanic language (English) into a high-context, agglutinative, Turkic language (Uzbek) creates significant structural tension. The study examines how English spatial-temporal subtitling limits encounter the heavy morphological volume of Uzbek verb complexes, forcing translators to rely on dramatic grammatical compression. Additionally, it analyzes the pragmatic constraints of adapting English conversational discourse markers and localized idiomatic expressions into Uzbek without losing narrative intent or violating cultural taboos. The paper demonstrates that stylistic equivalence in English–Uzbek AVT requires a dynamic compromise between grammatical economy, phonetic synchronization, and cultural transcreation.